Characterization and investigation of thanatin based antimicrobial peptides - Aw, Marcus Yu Kian (Nanyang Technological University, 2022)
With the rapid increase of multidrug resistant pathogens, thanatin, a 21-residue long antimicrobial peptide, has been identified as a potential alternative to antibiotics against Gram-negative bacteria, due to its potent dual mode of action involving cell-cell agglutination and outer membrane (OM) biogenesis disruptions. The present study aims to investigate and characterize two acylated thanatin I14M isoforms, C4-I14M and C8-I14M. Through MIC and checkerboard assays, NMR, fluorescence, and interaction studies, this study has examined antibacterial activity, vancomycin potentiation ability, structure, and binding with LPS and LptAm, a truncated form of LPS transport protein LptA. Despite lacking intrinsic antibacterial activity, both peptides demonstrated OM permeabilizing and vancomycin potentiating capabilities, with C8-I14M generally exerting greater effects than C4-I14M. Overall, the peptides showed greater OM permeabilization and surface charge reduction for Escherichia coli compared to Pseudomonas aeruginosa cells. Weak exothermic interactions were observed in ITC studies between the peptides with LPS and LptAm. Further, NMR studies delineated the importance of both the β-hairpin and dimeric structure of thanatin during LPS binding, where absence of the latter possibly explaining why C4-I14M was unable to inhibit bacterial cell growth. Overall, this study provides new insights for future developments of effective thanatin based short antimicrobial peptides.